2021
DOI: 10.1080/23288604.2021.1911067
|View full text |Cite
|
Sign up to set email alerts
|

Financial Protection in Health among the Elderly – A Global Stocktake

Abstract: Universal Health Coverage is one of the key targets of the Sustainable Development Goals and it implies that everyone can access the healthcare they need without suffering financial hardship. In this paper, we use a large set of household surveys to examine if older populations are facing different degrees of financial hardship compared to younger populations. We find that while differences in average age structures between countries are not systematically associated with higher financial risk related to outof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Nations across the world have adopted Universal Health Coverage (UHC) as the desired goal for health systems and ensuring protection from catastrophic health expenditures is central to it. Studies in India and other LLMICs have shown that hospitalisations of the elderly often lead to catastrophic expenditure for the elderly and their families [8,[13][14][15][16][17][18]. The occurrence of large OOPE on hospitalisations of the elderly poses a significant challenge to India's aim of achieving UHC, [8,11,19].…”
Section: Introductionmentioning
confidence: 99%
“…Nations across the world have adopted Universal Health Coverage (UHC) as the desired goal for health systems and ensuring protection from catastrophic health expenditures is central to it. Studies in India and other LLMICs have shown that hospitalisations of the elderly often lead to catastrophic expenditure for the elderly and their families [8,[13][14][15][16][17][18]. The occurrence of large OOPE on hospitalisations of the elderly poses a significant challenge to India's aim of achieving UHC, [8,11,19].…”
Section: Introductionmentioning
confidence: 99%
“…Using a different approach to compare incidence rates of catastrophic health spending among those living in households with different age structures but controlling for other possible confounders (e.g. socioeconomic status), a recent study confirms the large differences in financial hardship between younger and older households across countries, with people living in households with higher old-age dependency ratios facing the highest incidence of catastrophic health spending (34). Most importantly, the study finds that differences in incidence of catastrophic health spending between those living in older households and those living in younger ones is the strongest within the poorest quintile of a given country (Box 4).…”
Section: Low-incomementioning
confidence: 94%
“…A recent study by Eozenou et al (34) explores the relationship between the incidence of catastrophic and impoverishing health spending and household old-age dependency levels. The study was based on household survey data from 133 countries (representing 89% of the world population).…”
Section: Box 4: Worsening Of Catastrophic Health Spending With Age Is...mentioning
confidence: 99%
“…To understand the effect of old age members on household CHE, we derived a household measure, the Old-Age Dependency Ratio (OADR), defined as the ratio of old-age dependents (60 years and above) to members in the working-age (18-60 years). 24,32…”
Section: Group Variablesmentioning
confidence: 99%
“…2,31 The present study used the household old-age dependency approach to capture the effect of old-age members on household CHE. 32 Second, we used the capacity-to-pay approach for estimating CHE and estimated concentration curve as it addresses equity consideration. We also plotted a CHE curve across old-age dependency households as recommended in literature.…”
Section: Introductionmentioning
confidence: 99%